" إعادة تقييم التوضّعات البازلتية في الجبال الساحلية السّورية " (مثال: جوبة الربند) (Latakia University Journal -Basic Sciences Series, 2016)
توجد توضّعات بازلتية فاسدة ، وأخرى طازجة في جوبات السلسلة الساحلية الموازية لانهدام الغاب في مواقعها. أجريت عدّة دراسات حول منشأ وزمن توضّعها ، لكنّ أغلبها لم يكن جازماً في ذلك الوفت. تثبت هذه الدراسة أن البازلت الموجود في هذه الجوبات يعود عمره إلى زمنين مختلفين: الأوّل هو حدود الجوراسي مع الكريتاسي، أي أسفل الكريتاسي الأعلى خلال النيوكوميان، والثاني خلال دور النيوجين، لا سيّما عصر البليوسين مرافقاً لزمن تشكّل انهدام الغاب. Corrupt Basalt deposits and fresh Basalt deposits are in Jaubats of coastal range of Syria, which is parallel of Al-Ghab ridge. Many studies are executed for origin and time of these deposits, but the most of them was not exactly. This research give us that Basalt in Jaubats belong two different times: -   First is frontier of Jurassic-Cretaceous, low of upper cretaceous throw Newcomian . -   Second is throw Neogene in special Pliocene, which is coincide with Al-Ghab rift formation.